Chapter VI: Summary (Quarterly Journal of Economics, 1941)
Journal Article Chapter VI: Summary Get access The Quarterly Journal of Economics, Volume 56, Issue 1_Part_2, November 1941, Pages 146–153, https://doi.org/10.1093/qje/56.1_Part_2.146 Published: 01 November 1941